2021
DOI: 10.1007/s40843-021-1825-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the magnetocaloric response of high-entropy metallic-glass by microstructural control

Abstract: Non-equiatomic high-entropy alloys (HEAs), the second-generation multi-phase HEAs, have been recently reported with outstanding properties that surpass the typical limits of conventional alloys and/or the first-generation equiatomic single-phase HEAs. For magnetocaloric HEAs, non-equiatomic (Gd36Tb20Co20Al24)100−xFex microwires, with Curie temperatures up to 108 K, overcome the typical low temperature limit of rare-earth-containing HEAs (which typically concentrate lower than around 60 K). For alloys with x = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…In addition, exponent n as a function of temperature has been used for identifying the presence of multiphases in Gd-Tb-Co-Al-Fe HEAs [21,67]. The authors found broadened widths in the minima of n(T) curves for their samples, which attribute to the observed enhancement in the refrigerant capacity values.…”
Section: Mce Field Dependence Exponent Nmentioning
confidence: 99%
“…In addition, exponent n as a function of temperature has been used for identifying the presence of multiphases in Gd-Tb-Co-Al-Fe HEAs [21,67]. The authors found broadened widths in the minima of n(T) curves for their samples, which attribute to the observed enhancement in the refrigerant capacity values.…”
Section: Mce Field Dependence Exponent Nmentioning
confidence: 99%
“…Furthermore, their excellent mechanical properties and phase stability in a large temperature range makes them interesting for technological application, such as magneto-caloric devices [ 15 ] and antidiffusion and anticorosive coatings (see, for example, [ 16 ] for a review). Continuing our work on multicomponent compositionally complex metal alloys [ 17 , 18 , 19 , 20 , 21 , 22 ], we report here on the results of a systematic study of electronic properties (the electrical resistivity, superconductive transitions and Hall effect) on amorphous samples of two quinary TE-TL alloy systems and (from hereon and , respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitudes of the MC effect have a strong correlation with the corresponding magnetic phase transition (MPT); therefore, the investigation of the MC effects of magnetic materials can provide considerable valuable information for the better understanding of MPT [5][6][7][8][9]. Therefore, many magnetic materials have been synthesized and systematically determined with regard to the magnetic proper-ties, MPT, and MC performances not only to search for suitable candidates for active MR application at cryogenic and near room temperature but also to better understand the MPT of magnetic materials [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. However, a large gap still exists at the present stage between the practical MR application requirements and the performances of known MC materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the last several decades, investigations have been performed on the MPT and MC effects in the rare-earth (RE)-based materials in amorphous and crystallized states owing to the large magnetic moments of RE ions, which result in considerable MC effects [18][19][20][21][22][23][24][25]. Law and Franco [13] reviewed the MC performances in RE-based high-entropy alloys.…”
Section: Introductionmentioning
confidence: 99%